Humanist Engineering: Writing Prophecies and Media Adaptation at the post-Gutenberg Era - Callau Gonzalvo, Sergio (2016)
The crisis in education affects the humanities especially, but the successive attacks on them go beyond the irrelevancy of these antique knowledges in an increasingly commodified world. The earlier and stronger human beings familiarize themselves with new communication technologies, the more questions are raised around the potential educational or, directly, cognitive benefits of these new hyper-technologized media. It is necessary to understand and give appropriate answers to this new media galaxy whose communicative power reaches traditional and urban societies, and it is as inescapable to illiterate people as to the powerful communication lobbies. A small but significant set of texts is introduced in this context as it demands paying attention to the irreplaceable power of learning how to write in a systematic and hyperaware way so as the threat of global cognitive dystopia in the post-Gutenberg era is averted.